Persistent Tracheostomy after Organ Preservation Protocol in Patients Treated for Larynx and Hypopharynx Cancer - Estomba,Carlos Miguel Chiesa (2017)
Abstract Introduction Squamous cell carcinoma of the larynx is currently the second most common malignancy of the airway after lung cancer, and hypopharyngeal cancer accounts for fewer than 5% of head and neck cancers. The nonsurgical options for patients with this disease are related to significant long-term toxicities and the need for persistent tracheostomy, which adversely affects the quality of life of these patients. Objective To evaluate the need for tracheostomy, and the influence of this in the overall and specific survival rates of patients diagnosed with all stages of laryngeal carcinoma treated by chemoradiotherapy. Methods A retrospective study of patients diagnosed with laryngeal carcinoma was performed according to the criteria of the Union for International Cancer Control (UICC) and the American Joint Committee on Cancer (AJCC) 7th edition, in a tertiary hospital. Results A total of 21 patients were evaluated, 8 patients required a tracheotomy (31%) during the treatment protocol, 7 (35%) men and 1 (100%) women. According to subsite 4/4 patient with glottis cancer (p ≤ 0.001), 2/10 patients with supra glottis cancer and 2/7 patients with hypopharyngeal cancer. During follow up, just in 1 patient was possible to close the tracheostomy. Conclusion Persistent tracheostomy dependence after primary chemoradiation increases significantly the morbidity, and decreases the quality of life of those patients. Patients with glottis cancer are prone to need a tracheostomy, but no statistical difference regarding the oncological stage and the need for a tracheostomy were detected. A more thorough selection of the patients is needed to improve the quality of life and reduce permanent tracheostomy dependence.